Feasibility and impact of data-driven learning within the suicide prevention action network of thirteen specialist mental healthcare institutions (SUPRANET Care) in the Netherlands: a study protocol. Issue 8 (20th August 2018) - Setkowski, Kim; Mokkenstorm, Jan; van Balkom, Anton JLM; Franx, Gerdien; Verbeek- van Noord, Inge; Dongelmans, Dave A; Eikelenboom, Merijn; Gilissen, Renske
Abstract : Introduction: Improvement of the quality and safety of care is associated with lower suicide rates among mental healthcare patients. In The Netherlands, about 40% of all people that die by suicide is in specialist mental healthcare. Unfortunately, the degree of implementation of suicide prevention policies and best practices within Dutch mental healthcare services is variable. Sharing and comparing outcome and performance data in confidential networks of professionals working in different organisations can be effective in reducing practice variability within and across organisations and improving quality of care. Methods and analysis: Using formats of professional networks to improve surgical care (Dutch Initiative for Clinical Auditing) and somatic intensive care (National Intensive Care Evaluation), 113 Suicide Prevention has taken the lead in the formation of a Suicide Prevention Action Network (SUPRANET Care), with at present 13 large Dutch specialist mental health institutions. Data on suicide, suicide attempts and their determinants as well as consumer care policies and practices are collected biannually, after consensus rounds in which key professionals define what data are relevant to collect, how it is operationalised, retrieved and will be analysed. To evaluate the impact of SUPRANET Care, standardised suicide rates will be calculated adjusted for confounding factors. Second, the extent to which suicide attempts are being registered will be analysed with the suicide attempt data. Finally, professionals' knowledge, attitude and adherence to suicide prevention guidelines will be measured with an extended version of the Professionals In Training to STOP suicide survey. Ethics and dissemination: This study has been approved by the Central Committee on Research Involving Human Subjects, The Netherlands. This study does not fall under the scope of the Medical Research Involving Human Subjects Act (WMO) or the General Data Protection Regulation as stated by the Dutch Data Protection Authority because data are collected on an aggregated level.